Integrated multiomics approach identifies calcium and integrin-binding protein-2 as a novel gene for pulse wave velocity. Issue 1 (January 2016) - Mangino, Massimo; Cecelja, Marina; Menni, Cristina; Tsai, Pei-Chien; Yuan, Wei; Small, Kerrin; Bell, Jordana; Mitchell, Gary F.; Chowienczyk, Phillip; Spector, Tim D.
Abstract : Background: Carotid-femoral pulse wave velocity (PWV) is an important measure of arterial stiffness, which is an independent predictor of cardiovascular morbidity and mortality. In this study, we used an integrated genetic, epigenetic and transcriptomics approach to uncover novel molecular mechanisms contributing to PWV. Methods and results: We measured PWV in 1505 healthy twins of European descendent. A genomewide association analysis was performed using standardized residual of the inverse of PWV. We identified one single-nucleotide polymorphism (rs7164338) in the calcium and integrin-binding protein-2 ( CIB2 ) gene on chromosome 15q25.1 associated with PWV [β = −0.359, standard error (SE) = 0.07, P  = 4.8 × 10 –8 ]. The same variant was also associated with increased CIB2 expression in leucocytes (β = 0.034, SE = 0.008, P  = 4.95 × 10 –5 ) and skin (β = 0.072, SE = 0.01, P  = 2.35 × 10 –9 ) and with hypomethylation of the gene promoter (β = −0.899, SE = 0.098, P  = 3.63 × 10 –20 ). Conclusion: Our data indicate that reduced methylation of the CIB2 promoter in individuals carrying rs7164338 may lead to increased CIB2 expression. Given that CIB2 is thought to regulate intracellular calcium levels, an increase in protein levels may prevent the accumulation of serum calcium and phosphate, ultimately slowing down the process of vascular calcification. This study shows the power of integrating multiple omics to discover novel cardiovascular mechanisms. Abstract : Supplemental Digital Content is available in the text